Atypical arthritis revisited: Acute rheumatic fever - Binoy Shankar; Euden Bhutia; Dinesh Kumar (Wolters Kluwer Medknow Publications, 2016)
A 13-year-old boy presented with vague musculoskeletal pain and involvement of multiple small and large joints along with axial skeleton for the last 3 years, poorly responsive to aspirin. However, on account of presence of carditis and fulfilment of Jones criteria, a diagnosis of acute rheumatic fever (ARF) with atypical arthritis was made. We report this case to break the myth and sensitize pediatricians and rheumatologists to keep the possibility of atypical articular presentations, as in our case, in patients with ARF and prevent delayed diagnosis and treatment.